THE INFLUENCE OF MARKETING VOLUME AND MARKETING CHANNEL ON FRESH TIGER SHRIMP MARKETING MARGIN - Abd Rahim; Diah Retno Dwi Hastuti; Septaty Rahayu Ningsih (Universitas Negeri Makassar, 2018)
This study aims to analyze the influence of marketing volume and marketing channel to marketing margin of tiger shrimp. This study uses data based on the time dimension, ie cross-section that comes from primary data, then the method of analysis used multiple regression with exponential function model. The result of this research found that marketing volume have positive effect and marketing channel I have negative effect to tiger shrimp marketing margin, while marketing channel II has no effect to marketing margin of tiger shrimp.